Transcatheter aortic valve implantation (balloon-expandable versus self-expandable valves) - what echocardiographic parameters should we evaluted?. (4th February 2022) - Mauricio, AR; Goncalves, S; Santiago, H; Santos, L; Prata, S; Vaz, R; Ribeiro, F; Almeida, AG; Pinto, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Transcatheter aortic valve implantation (TAVI) is currently the recommended treatment for aortic stenosis (AS) in high or intermediate-risk or inoperable patients. Balloon-expandable valve (BEV) and self-expanding valve (SEV) are the two major types of transcatheter heart valves (TTHV). Despite major diferences, both designs are recomended, however, there are only limited data available for the comparison of newer generation BEV and SEV. Purpose: Compare echocardiographic and clinical parameters, during 1 year of follow-up of a balloon-expandable (BS) versus self-expanding (SE) transcatheter aortic valve implantantation, with emphasis on the composite endpoits proposed by uptade Valve Academic Researc Consortium (VARC-2). Methods: Retrospective, comparative study in patients with symptomatic severe AS with a high operative risk, who implanted BEV or SEV between January 2016 and December 2019. All patients underwent echocardiographic study before an after the procedure (on the day, 6 months and 1 year of follow up), clinical data were collected. The following ecocardiographic parameters were evaluated: transvalvular and prosthetic aortic gradientes and paravalvular leak (PVL). Results: We studied 106 patients (81 ± 8 years, 60% female) with severe AS (mean gradient of 49 ± 12 mmHg), who were threated with BE or SE transcatheter aortic valve. Comparative analysis between BEV vs SEV, showed: there were no statistically significant in mean transprosthetic gradients (9.5 ± 4.8 vs 10 ±6.2; p = 0.49). There were no statistically significant differences between BE and SE valves in the cumulative incidence of death from any cause (21% vs. 28%; p = 0.49), death from cardiovascular causes (3.3% vs. 0%; p= 0.26), all strokes (1.6% vs. 1.6%; p = 0.85), pacemaker implatation (18% vs. 15% p = 0.79); major bleeding (3.3% vs 6.5%; p = 0.18) and renal injury (1.6% vs. 2.1%: p = 0.67). There were statistically significant differences between BE and SE valves in the cumulative incidence of moderate or severe PVL (5% vs. 23.9%; p = 0.009) and repeat hospitalization (11.6% vs. 28%;p = 0.04). Device sucess was achieved in 97 % for BEV vs 91% for SEV (p = 0, 39). The early safety at 30 days was observed in 5% for BVE vs. 4.3% for SVE (p = 0.87). The clinical efficacy after 30 days was achieved in 1, 6% for BVE vs. 4.3% for SVE (p = 0.03), with higher incidence of moderate or severe PVL. The composite endpoint valve safety occured in 3, 3 % for BVE vs 26% for SVE (p < 0, 001), with moderate or severe PVL in 23%. Conclusion(s): In patients with symptomatic severe aortic stenosis who implanted BEV or SEV transcatheter aortic valve there was a significant improvement in the hemodynamic status. The present study suggests that use of SEV was associated with a higher risk of PVL and repeat hospitalization, with a endpoint clinical efficacy after 30 days (4, 3%) and time-related valve safety (26%).